Evaluation of sensory component of psycho-physiological state qualified fighters in the dynamics of accruing efficiency - Тоmaschuk V.S; Ilyin V.M; Muhаilоvich М.М (Kharkov National Pedagogical University, 2010)
Sensory components of a psychophysiological condition with the help of a computer system of diagnostics are construed. 11 sportsmen of a high class of a combined team of Ukraine have been inspected. It is exhibited, that in dynamic of increasing serviceability at sportsmen the tendency to improving parameters of a sensory component of a psychophysiological condition is marked. The estimation of psychophysiological condition of an organism of sportsmen with the help of differentiated scales enables to adjust training loadings in dynamic of increasing serviceability.